Analisis Semantik terhadap Nama Diri Mahasiswa - NFN Hermandra (SUAR BETANG, 2022)
The most important part of proper names which is related to the language is form and the types of meaning. This research reviews the language form and types of proper names meaning of students in the Indonesian Language and Literature Education Study Program, University of Riau, class of 2020. The purpose of this study is to describe the language form and the types of meanings of students’ proper names. This is descriptive-qualitative research. The research was carried out in three stages, namely providing the data, analyzing the data, and presenting the result of the analysis. The data is tabulated and divided into two sections, the forms and the meaning of those proper names. Based on the analysis, several proper names use three different kinds of languages, namely Malay, Javanese, and Arabic. The meaning of students’ proper names also contains certain kinds of prayers from parents to their children.AbstrakBagian terpenting dari nama diri yang berhubungan dengan bahasa ialah bentuk dan maknanya. Makalah ini mengkaji bentuk dan makna nama diri mahasiswa rogram Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Riau angkatan 2020. Tujuan penelitian ini adalah memaparkan bentuk dan makna nama diri mahasiswa tersebut. Penelitian ini merupakan penelitian deskriptif-kualitatif. Penelitian dilaksanakan dalam tiga tahap, yaitu penyediaan data, analisis data, dan penyajian hasil analisis. Data ditabulasi dalam bentuk tabel yang terbagi atas dua aspek, yaitu bentuk dan makna nama diri. Berdasarkan analisis, ada beberapa bahasa yang digunakan sebagai nama diri mahasiswa, yaitu Melayu, Jawa, dan Arab. Nama diri juga mengandung doa dan harapan orang tua terhadap anak-anak mereka.